2020
DOI: 10.1177/2397791420905236
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of porous hydrostatic journal bearing under micropolar fluid lubrication

Abstract: The features of micropolar fluid (a non-Newtonian fluid)–lubricated short single-layered porous hydrostatic journal bearing are analyzed theoretically by an iterative method. To investigate hydrostatic journal bearing characteristics, a modified Reynolds equation in the case of micropolar fluid is derived and solved numerically. The obtained results in this work are validated by comparing the same with previously published results with Newtonian and non-Newtonian lubricants in the form of design charts. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
0
15
2
Order By: Relevance
“…Figure 2 illustrates the change in the coefficient of stiffness with the bearing number and additionally, it also shows a comparison of present outcomes with the consequences of Ref. [11]. The components (K xx and K yy ) of the stiffness coefficient of the current examination are improved as contrasted with the same of micropolar fluid [11].…”
Section: Stiffness Coefficientmentioning
confidence: 80%
See 4 more Smart Citations
“…Figure 2 illustrates the change in the coefficient of stiffness with the bearing number and additionally, it also shows a comparison of present outcomes with the consequences of Ref. [11]. The components (K xx and K yy ) of the stiffness coefficient of the current examination are improved as contrasted with the same of micropolar fluid [11].…”
Section: Stiffness Coefficientmentioning
confidence: 80%
“…In this section, the advantage of utilizing nano-lube oil over micropolar oil has been talked about extravagantly. For the purpose of valid approval of established results, Shenoy et al [10] and Bhattacharjee et al [11] are surveying the findings of the existing analysis similar to those obtained. The design graphs and tables demonstrated that the present hypothetical examinations are in acceptable understanding (Table 1).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations